Spatiotemporal dynamics of soil erosion response to land use land cover dynamics and climate variability in Maybar watershed, Awash basin, Ethiopia - Wudu Abiye; Istvan Waltner; Hailu Kindie (Geology, Ecology, and Landscapes)
Soil erosion is a global problem that threatens sustainability and food security by washing away fertile soil, nutrients, and organic matter. Land use changes, land degradation, and soil erosion are increasing, resulting in annual losses of fertile soil and declining crop yields. The objective of this study was to examine how changes in land use and land cover affected soil erosion dynamics and determine which areas should receive priority for soil and water conservation interventions. The study employs remote sensing and Geographic information system techniques to assess the impact of land use and land cover change on soil erosion between 2004 and 2020. The RUSLE model estimates soil erosion rates. Mean annual rainfall, soil data, 2 m DEM, and satellite images are used to input data into the model to determine soil erosion. The study identifies six land use and cover types and shows that significant changes have occurred in bare land and shrubland, decreasing by 25.48% and 6.17%, respectively, from 2004–2020. On the other hand, forest land increased by 20.19%, and cultivated land increased by 3.52%. Additionally, the study evaluated the response of soil erosion to land use and land cover changes, showed that bare land, cultivated land, and grazing land have the highest annual loss. In contrast, forest land, shrubland, and water bodies have the lowest. The analysis of soil erosion risk indicated a decline in the mean annual soil loss rate at the watershed scale, with rates decreasing from 12.8t ha−1 yr-1 in 2004 to 3.21t ha-1 yr-1 in 2020. The watershed is classified into five severity classes, and the study area was divided into five priority categories based on their average annual soil losses. The study emphasized that prioritizing interventions for watershed types with high erosion risks is crucial for reducing on-site soil loss and off-site effects together with conserving water resources. The findings support the importance of long-term watershed management in reducing soil erosion. To effectively reduce soil erosion and improve environmental quality, it is recommended to encourage afforestation and reforestation, develop sustainable land use policies, strengthen soil conservation measures, and improve monitoring and evaluation of land use changes.